Boosting productivity and living standards in Thailand - Koen, Vincent 1960- (OECD Economics Department Working Papers, 2018)
The Prosperity pillar of the 2030 Agenda for Sustainable Development calls for an integrated approach based on boosting productivity through diversification, upgrading technology and innovation, and increasing employment and entrepreneurship. Thailand needs to address all these challenges to achieve high-income country status by 2036. Over the past decade, limited structural reform and capital investment have held back productivity growth and improvements in well-being, and Thailand has lost ground vis-à-vis regional comparators. More recently, however, economic growth has started to regain momentum helped by a pick-up in global trade, which has supported exports, and by a substantial public infrastructure investment programme. Moving forward, Thailand will need to boost productive capacity in the face of intensified competition with regional peers and rapid demographic ageing. In addition, productivity gains will be increasingly necessary to drive growth. Key areas of focus include improving human resource development, encouraging technology diffusion via cluster development, promoting innovation and digitalisation, improving the SME policy framework and expanding regional integration, as emphasised in the government's 12th Plan and Thailand 4.0. This Working Paper relates to the Initial Assessment report of the Multi-dimensional Country Review of Thailand (http://www.oecd.org/eco/surveys/multi-dimensional-review-thailand.htm)